2012
DOI: 10.1007/978-3-642-27355-1_55
|View full text |Cite
|
Sign up to set email alerts
|

Asserting the Precise Position of 3D and Multispectral Acquisition Systems for Multisensor Registration Applied to Cultural Heritage Analysis

Abstract: Abstract. We present a novel method to register multispectral acquisitions on a 3D model. The method is based on the external tracking of the acquisition systems using close-range photogrammetric techniques: multiple calibrated cameras simultaneously observe the successive acquisition systems in use. The views from these cameras are used to precisely determine the position of each acquisition system. All datasets can then be projected in the same coordinate system. The registration is thus independent from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When the acquisition systems are fixed to this target frame and survey an area of 400 mm × 700 mm, the simulations [30] show that we can achieve a spatial tracking accuracy of 0.020 mm and an angular accuracy of 0.100 mrad using four tracking cameras. Equivalent tracking accuracy can be obtained using six cameras when the acquisition systems digitize an area of 2,000 mm × 1,500 mm, such as a wall-painting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the acquisition systems are fixed to this target frame and survey an area of 400 mm × 700 mm, the simulations [30] show that we can achieve a spatial tracking accuracy of 0.020 mm and an angular accuracy of 0.100 mrad using four tracking cameras. Equivalent tracking accuracy can be obtained using six cameras when the acquisition systems digitize an area of 2,000 mm × 1,500 mm, such as a wall-painting.…”
Section: Methodsmentioning
confidence: 99%
“…Simulations have shown that it is possible to track our acquisition systems with an accuracy of 0.014 mm spatially and 0.100 mrad angularly [30]. This paper presents the experimental results performed in a laboratory environment to test the feasibility and the accuracy of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic implemented procedure included: automatic detection of a common region between overlapping textured 3D views, pairwise registration of 3D views, global registration, multi-spectral texture construction and surface fusion. Simon et al (2012) and Chane et al (2013) applied photogrammetric tracking on pre-calibrated multispectral cameras and fringe projection systems for 3D digitization used on the same scenes, to co-register and project the multi-spectral data on 3D models of heritage surfaces, with accuracy better than half an image pixel. Pelagotti et al (2009) and Remondino et al (2009) extracted depth maps from 3D heritage models, whose pixels maintained correspondence with the vertices of the respective 3D models, to register those maps with texture from multispectral images through Maximization of Mutual Information algorithms.…”
Section: Spectral and Multi-spectral Imagingmentioning
confidence: 99%